Acute residual effects of short and long duration static stretching on counter movement jump performances in well-trained female combat athletes - Pekünlü, E.; Sagiroglu, I.; Kurt, C.; Özsu, I. (European Journal of Physical Education and Sport Science, 2016)
Duration of static stretching is the most crucial factor associated with static stretch-induced impairments in explosive muscular performances. The aim of this study was to investigate the acute residual effects of lower body short (S-SS) and long duration static stretching protocols (L-SS) on counter movement jump (CMJ) performances in skilled female combat athletes. Twelve well-trained female combat athletes (training experience: 11.5 ± 3.6 years) performed S-SS (6 min of total stretch duration) and L-SS (12 min of total stretch duration) separated by 48 hours in a randomized, balanced order. After each protocol, participants performed, respectively, counter movement jump with arm swing (CMJAS) and with hands on hip (CMJHH) separated by 30-second rest interval at the 15th second and 1st, 5th, 10th, 15th, and 20th minute of the 20-minute recovery period. An insignificant interaction effect was found for Protocol × Time in CMJ heights (p = 0.722) indicating that both S-SS and L-SS reduced CMJ heights to a similar extent over the course of 20 min recovery period. S-SS and L-SS led to a mean CMJ height reduction of 6.29% (p < 0.05, d = 0.603) and 6.74% (p < 0.05, d = 0.610), respectively. Greater than 50% of participants experienced a reduction in CMJAS height exceeding minimum detectable change score with 90% confidence at each time point during the recovery period without exception. Use of static stretching protocols = 6 minutes prior to competitions and/or training sessions may lead to impairment in lower body explosive strength of well-trained female combat athletes that persists at least 20 minutes. This impairment may also indirectly hinder their sport-specific performance since combat sports include a great deal of movement patterns related to lower body explosive strength.